Illness Perception and Self-care Behaviors of Thai Muslim Patients with Coronary Artery Disease in the Three Southernmost Provinces - Sangsuwan, Chortip; Charoenwong, Suangsuda; Tongnuang, Patcharawadee (Princess of Naradhiwas University Journal, 2025)
Background and Objective Coronary artery disease is one of the leading causes of death in Background and Objectives: Coronary artery disease was a leading cause of death overall. A significant issue was the recurrence of treatment due to self-care behaviors. The perception of illness affected self-care behaviors, influenced by external stimuli within the social and cultural context. The three southernmost provinces have a lifestyle that differs from other areas. This research aimed to study the relationship between illness perception and self-care behaviors of Thai Muslim patients with coronary artery disease in the three southernmost provinces. Method A multi-stage random sampling method based on specified criteria, with a total of 112 participants. The research instruments included 1) a personal information and health condition questionnaire, 2) an illness perception questionnaire, and 3) a self-care behavior scale. Content validity was assessed by three experts, and the reliability of the illness perception questionnaire was tested using the test-retest method, yielding a coefficient of 0.93. The Cronbach’s alpha coefficients for disease causes, other illness perceptions, and self-care behaviors were 0.80, 0.80, and 0.82, respectively. Data collection was conducted from November 2024 to January 2025, and the data were analyzed using descriptive statistics and Pearson's product moment correlation coefficient. Results The sample group perceived the symptoms related to the disease, with the most common being shortness of breath (93.80%). This was followed by chest pain lasting more than 20 minutes and palpitations (83.90% and 83.00%, respectively). In terms of the perceived causes of the disease, the most common belief was that it was the will of God (x̄ = 3.88, S.D. = 0.39), followed by smoking (x̄ = 3.36, S.D. = 1.03) and aging or senescence (x̄ = 3.30, S.D. = 0.87). For the illness perception in 6 aspects, it was found that the perception of illness cure and controllability by treatment control and personal control, as well as the illness coherence, were at a high level (x̄ = 3.60, S.D. = 0.26; x̄ = 3.18, S.D. = 0.29; x̄ = 3.14, S.D. = 0.57, respectively). The perception of timeline, consequences, timeline cyclical, and emotional representations were at a moderate level (x̄ = 3.08, S.D. = 0.80; x̄ = 2.84, S.D. = 0.50; x̄ = 2.78, S.D. = 0.63; and x̄ = 2.11, S.D. = 0.62, respectively). Overall self-care behaviors were at a moderate level (x̄ = 2.87, S.D. = 0.40). The perception of the illness timeline had a negative correlation with exercise behavior (r = -.187, p < .05). The perception of illness in terms of the cure and controllability by treatment control had a negative correlation with stress management behavior (r = -.195, p < .05), and the perception of illness in terms of emotional representations had a negative correlation with the treatment plan adherence (r = -.248, p < .01) Conclusion and Recommendation From the research findings, it was found that the perception of illness in each area did not correlate with overall self-care behavior. However, there are negative correlations in specific areas, and the average scores for exercise and diet behaviors were low. Therefore, healthcare personnel teams should develop self-care models and programs that promote perception and self-care behaviors in patients with coronary artery disease according to the social and cultural contexts of the three southernmost provinces. This will help patients have a better understanding of their illness perception and adopt more appropriate self-care behaviors.